Des sources comptables au service de l’archéologie : essai de reconstruction documentaire de la chapelle dite Saint-Nicolas du château de Falaise (Calvados), XIIe-XVe siècles - Isabelle Chave (Tabularia)
Destroyed in 1944, the sanctuary built in the yard of the Castle of Falaise (Calvados) is not well known. Clearly stated, the typological problems raised by the remains dug up during an archaeological boring investigation have nevertheless been poorly explained. Medieval accouting vouchers, modern texts and a rich collection of pictures dating from about 1750 to 1880, enable a re-interpretation of these observations and a reassessment of the status of the Castle Chapel of Saint-Nicolas which was served in the Middle Ages by the clergy of the Saint-Jean Abbey in Falaise.